Linking a multidimensional construct of networking self-efficacy to firm growth. Issue 1 (1st January 2019) - Bratkovič Kregar, Tina; Antončič, Boštjan; Ruzzier, Mitja
Abstract: The purpose of the study is to develop a multidimensional construct of networking self-efficacy, empirically test its multidimensionality, and analyse its relationship to firm growth. The empirical study is based on data collected through a structured questionnaire that was emailed to entrepreneurs from small- and medium-sized firms in Slovenia. The developed scale was examined for convergent and discriminant validity with exploratory and confirmatory factor analyses. The predictive validity of the scale was measured by linking networking self-efficacy to firm growth. The results confirmed a three-dimensional structure of the networking self-efficacy construct and a positive relationship between networking self-efficacy and firm growth. The results of the study show that a stronger sense of networking self-efficacy can actually result in greater network support and consequently also better firm growth. Thus, entrepreneurs should be confident in their abilities to obtain and efficiently use resources acquired through their personal networks in order to exploit all the benefits of their social networks.